Effect of steam blanching and high temperature drying on the physicochemical properties, antioxidant activities and consumer acceptability of Hibiscus cannabinus leaves tea - Haw, Yen Teng; Sim, Yan Yi; Nyam, Kar Lin (Journal of food science and technology, 2020)
Kenaf ( Hibiscus cannabinus ) leaves are produced as the by product when kenaf stems were harvested. The kenaf leaves was examed for the applicable possibility as herbal tea due to their rich phenolic content. In this study, the effect of steam blanching and high temperature drying on physicochemical properties, antioxidant activity and consumer acceptability of the kenaf tea leaves were studied. Results showed that steam blanching prior oven-drying improved the extractability of phenolic compounds, leading to the increase in total flavonoid content, 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity, and ferric reducing antioxidant power. Drying at 120 °C was able to preserve more phenolic compounds, at the same time developing better taste, mouthfeel, and overall acceptability of kenaf leaves tea. Caffeic acid, tannic acid, catechin, and chlorogenic acid in kenaf tea leaves infusion were analyzed by ultra high performances liquid chromatography. In conclusion, steam blanching prior to 120 °C oven-drying was the best process method for the production of kenaf leaves into acceptable tea type.